Australian vegetation - Turnbull, J.W. (1997)
The volume is designed to provide a reference text for all those concerned with selecting and growing trees and shrubs in rural areas of developing countries and in the more tropical parts of Australia. This first chapter highlights the uniqueness of Australian vegetation and its evolution and its place as a typical segment of the world's flora. The woody plants of Australia have been noted for their uniqueness from the time of their discovery and study by European botanists. How different they are is a matter of interpretation, but a degree of uniqueness derives from the fact that some 75% of the species are endemic to Australia and the woody vegetation over most of the continent is dominated by two large genera, Eucalyptus and Acacia. At a higher taxonomic level, almost all angiosperm families in Australia occur widely in other parts of the world. The special character has to be explained in terms of the geography and environment in which they have evolved. Prolonged isolation of Australia following the break-up of the southern super-continent of Gondwana has contributed greatly to the distinctiveness of the vegetation. Australia has been isolated from other continents for at least 60 million years. During this period, great changes occurred in the climate and soil, which were important in the evolution of the modern flora.